GAMBARAN FAKTOR-FAKTOR PENYEBAB TERJADINYA STROKE - Risa Nur Pajri Ds; Safri Safri; Yulia Irvani Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Stroke is a serious neurological disorder, ranks high cause of death after cardiovascular disease and cancer that isinfluenced by many risk factors such as uncontrollable factors such as age, sex, race, and controllable factors such ashistory of hypertension, history of diabetes mellitus, obesity and cholesterol. This study aims to determine how thedescription of risk factors for stroke in Rejosari Pekanbaru Health Center. This study is a descriptive study usingsecondary data of stroke patients. Data taken in the form of education, occupation, age, gender, race, history ofhypertension, history of diabetes mellitus, obesity and cholesterol, research sample are all stroke patients coming toRejosari Pekanbaru Health Center that meet Inclusion Criteria. The results showed the highest proportion of strokewas ischemic stroke (93.3%), high school education (26.7%), and worked as private (50%). The highest uncontrollablerisk factors were age 51-65 years (50%), male gender (66.3%), history of hypertension (73.3%), no history of diabetesmellitus (56.7%). obesity (63.3%) and cholesterol (66.7%) .The researcher hoped that the result of this research can beused as input for health workers, especially the nurses who work in Puskesmas Rejosari Pekanbaru to provideinformation about the causes of stroke to stroke patients.Keywords: Risk factors, Stroke, ischemic